Alterações metabólicas, qualidade de vida e capacidade funcional de idosos atendidos na estratégia de saúde da família de um munícipio de Goiás - Avelar, Ivan Silveira de (2016)
Aging involves neural structural, functional and chemical changes that generate a number of diseases. Among the diseases that affect the elderly stand out metabolic and functional, such as metabolic syndrome and loss of muscle strength, which are closely related to the quality of life and are influenced by inadequate nutritional status and physical inactivity. Studies show that protein supplementation can increase muscle strength and improve body composition. The objective of the study was to evaluate the metabolic changes and the quality of life as well as the effects of a water aerobics program associated with supplementation of soy protein in muscle strength, hydration status and body composition of the elderly. The research began with the participation of 63 elderly aged ≥ 60 years. We determined the frequency of metabolic syndrome and assessed the quality of life of those with and without SM, using the SF-36. Still, the elderly were subjected to a water aerobics program associated with supplementation of soy protein for six months and evaluated for manual pressure force by force transducer manual, and state hydration and body composition by BIA. The normality of the data was assessed by the Shapiro-Wilk. The Mann-Whitney test was used to compare the variables of MS and the scores of quality of life between the groups with metabolic syndrome (CSM) and without metabolic syndrome (SSM). The scores of each SF-36 domain were divided into tertiles and associated with individuals with and without MS using the chi-square test of Pearson (2). In the study evaluating the effect of water aerobics program with or without supplementation used the Student t test for independent samples to compare the variables with normal distribution between the groups and the Mann-Whitney test to compare variables without normal distribution. In the above analysis we used the SPSS software and adopted the significance level of p <0.05. The vectors of BIVA were analyzed by Hotelling's T2 tests and univariate analysis (F test). The distances between the vectors in each group were correlated, was also calculated and, using Mahalanobis distance D (D). The vectors were analyzed using the software BIVA 2002. The effect of supplementation on strength and body composition was assessed by analysis of variance (ANOVA) for repeated measures with Bonferroni post hoc. The results indicated a prevalence of 79.03% of elderly patients with metabolic syndrome. There was no difference between the domains of quality of life among older people with and without MS. qualitative improvement was observed in the above hydration. The study indicated a high frequency of metabolic syndrome but did not affect the quality of life of the studied group. The manual force had a significant increase (p=0.001) in the group that underwent aquatic exercise performed and consumed the soy protein supplement. Fat-free mass was significant loss in the group that used the protein supplement. The practice of gymnastics, with or without supplementation increased the manual pressure force, but did not change the body composition of the elderly.